Blood, toil, tears, and sweat Winston Churchill's famous speeches - Churchill, Winston (Cassell, 1989)
With a superb series of specially selected illustrations, & a pithy introduction to each speech by Cannadine, this collection gives an unforgettably vivid picture of Churchill the orator in action. His voice may be silenced, but his words still speak.